2007
DOI: 10.1002/smi.1159
|View full text |Cite
|
Sign up to set email alerts
|

Perceived psychosocial stress and cardiovascular risk: observations among the Bhutias of Sikkim, India

Abstract: Psychosocial factors (including psychosocial stress) are documented to be related to morbidity and mortality due to cardiovascular diseases (CVDs) and their risk factors. The present study examines whether perceived psychosocial stress affects blood pressures, blood lipids and obesity among the Bhutias, a tribal population of Sikkim. A total of 428 Bhutias of both sexes aged 20 years and above inhabiting both urban and rural areas participated after providing informed consent. Data on blood pressures, blood li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
0
9
1
Order By: Relevance
“…This is important because central obesity is associated with increased susceptibility to chronic diseases including type 2 diabetes (De Pablos-Velasco et al, 2002;Carey et al 1997) and cardiovascular disease (Kannel et al 1991). Psychosocial factors, including stress, have been implicated as a risk factor for obesity and increased adiposity (Ishizaki et al, 2008;Lloyd et al, 1996;Sarkar and Mukhopadhyay, 2008), and the increased propensity toward obesity in women in our sample may thus be related to stress stemming from unequal status and domestic violence, as discussed above. Overall, women face increased risks for non-communicable diseases in Vanuatu as compared to men, information which can be translated into targeted intervention strategies for obesity in Vanuatu.…”
Section: Contributors To Differences In Male-female Obesity Prevalencementioning
confidence: 73%
“…This is important because central obesity is associated with increased susceptibility to chronic diseases including type 2 diabetes (De Pablos-Velasco et al, 2002;Carey et al 1997) and cardiovascular disease (Kannel et al 1991). Psychosocial factors, including stress, have been implicated as a risk factor for obesity and increased adiposity (Ishizaki et al, 2008;Lloyd et al, 1996;Sarkar and Mukhopadhyay, 2008), and the increased propensity toward obesity in women in our sample may thus be related to stress stemming from unequal status and domestic violence, as discussed above. Overall, women face increased risks for non-communicable diseases in Vanuatu as compared to men, information which can be translated into targeted intervention strategies for obesity in Vanuatu.…”
Section: Contributors To Differences In Male-female Obesity Prevalencementioning
confidence: 73%
“…Ho and Chan report that "In Hong Kong China, increasing BMI was associated with a lower number of sleeping hours and increasing working hours, suggesting an intimate relationship between physical health and psychosocial stress … with obesity as one of the major risk factors" (2008: 35). In a study of the Bhutias, a tribal people in the Himalayas, Sarkar and Mukhopadhyay (2007) found that those living in towns suffered more perceived psychosocial stress and consequently greater prevalence of obesity.…”
Section: A World Health Problemmentioning
confidence: 99%
“…with obesity as one of the major risk factors” (2008: 35). In a study of the Bhutias, a tribal people in the Himalayas, Sarkar and Mukhopadhyay (2007) found that those living in towns suffered more perceived psychosocial stress and consequently greater prevalence of obesity.…”
Section: A World Health Problemmentioning
confidence: 99%